Servo motor sliding mode control based on fuzzy power index method. (September 2021) - Li, Ye; Wang, Dazhi
Abstract: A servo motor sliding mode control system based on the fuzzy power exponent approach rule is proposed in this paper. The clearance gear of the leaf spring is studied in agreement with the basic configuration of the real servo motor. The definition of the proposed fuzzy power index approach law and the sliding mode theory, the error of two sub motors is established. The control torque is obtained by implementing the sliding film switching function, and the control of the motor sliding mode is done by monitoring the output shaft of the rotor. To check and evaluate the experiment results, MATLAB's simulation platform is used. The proposed control method will better monitor the actual track of disturbance signal shift and achieve reliable servo motor control sliding mode control.